Artificial Intelligence vs. Autonomous Decision-Making in Streaming Platforms - Gonçalves, Ana Rita (2024)
Gonçalves, A. R., Pinto, D. C., Shuqair, S., Dalmoro, M., & Mattila, A. S. (2024). Artificial Intelligence vs. Autonomous Decision-Making in Streaming Platforms: a Mixed-Method Approach. International Journal Of Information Management, 76, 1-12. Article 102748. https://doi.org/10.1016/j.ijinfomgt.2023.102748 --- %ABS2% --- This work received partial support from national funds through FCT (Fundação para a Ciência e a Tecnologia), under the projects - UIDB/04152/2020 and DSAIPA/DS/0113/2019 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.